2020
DOI: 10.1111/1742-6723.13640
|View full text |Cite
|
Sign up to set email alerts
|

Displaying emergency patient estimated wait times: A multi‐centre, qualitative study of patient, community, paramedic and health administrator perspectives

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The outcome choices and definitions were informed by a large, multisite, qualitative study of community members, consumers, paramedics and health administrators. [5] These participants recommended a prediction accuracy of +/-30 minutes (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome choices and definitions were informed by a large, multisite, qualitative study of community members, consumers, paramedics and health administrators. [5] These participants recommended a prediction accuracy of +/-30 minutes (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of this study was determined by a qualitative study involving patients, the public and other stakeholders. [5] Consumers and community stakeholders contributed to the design and write up of the study.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose a single prediction based on consumer feedback that triage categories are not understood by patients and families. [5] Ang et al modelled low-acuity patients only and reported performance in terms of Mean Squared Error, arguing that median based measures tend to underestimate due to right skewed distribution of wait-times. [7] We observed this with Rolling Average models, but not others.…”
Section: Discussionmentioning
confidence: 99%
“…We recently published a Victorian qualitative study, conducted in ED waiting rooms, the community and health service offices, which explored ED stakeholder views on wait time visibility. 1 Wait time visibility was important to patients, families and paramedics but we did not investigate which wait times consumers valued the most. Emergency medicine operations literature generally assumes that door-to-provider is the most important wait time for patients and families.…”
mentioning
confidence: 99%